Faktor-Faktor Penyebab Utang Luar Negeri dan Dampaknya Terhadap Pertumbuhan Ekonomi Indonesia - Nunu Nugraha; Kamio Kamio; Diah Setyorini Gunawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research aims to examine and analyze the effect of government spending, exchange rate, and Debtor economic growth on Indonesia's foreign debt, as well as the impact of external debt on economic growth. The tools of the analysis in this research used multiple linear regression method and use test (t-test and F-test). The result of study indicated government expenditures have a significant effect on foreign debt while debtor country exchange rate and economic growth have no significant effect on external debt. Simultaneously government spending, debt country,  exchange rate and economic growth significantly affected Indonesia's foreign debt in 2001-2017. Meanwhile, foreign debt has  significant effect on economic growth in Indonesia in 2001-2017.